Nuvens carregadas de ideias: o Engraçado e o Sério entre Estrepsíades e Sócrates na Comédia de Aristófanes - Almeida, Solange Maria Soares de (2012)
It is analyzed at this dissertation, by comparative study of the play Clouds and of some Plato’s dialogues, what is funny and serious among Strepsiades and Socrates, both characters of the Aristophanes’ comedy. Based on the research and the subsequent study of the texts fragments from physicists or philosophers of nature, nowadays called the Presocratics, an attempt is done to explain some scientific theories used in the play. Different situations of confrontation among the two characters selected for this study are discussed with the support of theoretical texts. Another relevant aspect in this study is the search of correlations among comic Poetry and Philosophy, to do this some of the Platonic dialogues are used as source. Even though these texts occurred after the play, they help to compose the picture that the philosopher had of Aristophanes, for example, when he has chosen him as the only representative of Comedy in Symposium. As Socrates aristofânico is also an object of study, is necessary comparing him to the Platonic Socrates, not with the intent to point out who is the "true", but in helping to understand the first.